Antioxidant Activity of Bawang Lanang (Allium sativum) as a Natural Product-Based Drug Candidate: A Potential Pharmacological Review - Auliya, Shafa; Amin, Saeful (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2025)
Developing natural product-based drugs with antioxidant activity represents a promising field in medicinal chemistry. This research aims to examine the potential of bawang lanang (Allium sativum) as a source of natural antioxidants that can be developed into drug candidates. The review method employs a systematic analysis approach to research related to the antioxidant activity of bawang lanang, biochemical mechanisms, and development prospects in medicinal chemistry. The results showed that the ethanol extract of bawang lanang bulbs has strong antioxidant activity with an IC₅₀ value of 13.85 ppm. In comparison, the ethyl acetate fraction exhibits higher activity with an IC₅₀ of 7.27 ppm. Phytochemical analysis identified the presence of flavonoids, saponins, and tannins that contribute to antioxidant activity. The antioxidant potential of bawang lanang is estimated to derive from organosulfur components, especially allicin and its derivatives, which can scavenge DPPH free radicals. Structural modification of bawang lanang bioactive compounds through medicinal chemistry approaches can potentially improve bioavailability and reduce side effects. In conclusion, bawang lanang has great prospects for development as an antioxidant drug through medicinal chemistry approaches with optimization of active compound structures, pharmacokinetic studies, and toxicity evaluation.